High levels of brain-derived neurotrophic factor are associated with treatment adherence among crack-cocaine users. (6th September 2016) - Scherer, Juliana N.; Schuch, Silvia; Ornell, Felipe; Sordi, Anne O.; Bristot, Giovana; Pfaffenseller, Bianca; Kapczinski, Flávio; Kessler, Felix H.P.; Fumagalli, Fabio; Pechansky, Flavio; von Diemen, Lisia
Highlights: Higher levels of BDNF were found in subjects who completed inpatient treatment. It was found a negative correlation between BDNF levels and years of crack use. TBARS levels tended to decrease in the completer group during inpatient treatment. We add evidence that BDNF and TBARS could be used to better understand crack abuse. Abstract: Due to the complexity of crack -cocaine addiction treatment, the identification of biological markers that could help determining the impact or outcome of drug use has become a major subject of study. Therefore, we aim to evaluate the association of Brain-Derived Neurotrophic Factor (BDNF) and Thiobarbituric Acid Reactive Substances (TBARS) levels in crack -cocaine users with treatment adherence and with drug addiction severity. A sample of 47 male inpatient crack- cocaine users were recruited in a treatment unit, and blood samples were collected at admission and discharge in order to measure BDNF and TBARS serum levels. Subjects were split into 2 groups: treatment non-completers (n = 23) and treatment completers (n = 24). The completer group had a tendency of higher levels of BDNF than non-completers at admission (16.85 ± 3.24 vs. 14.65 ± 5.45, p = 0.10), and significant higher levels at discharge (18.10 ± 4.88 vs. 13.91 ± 4.77, p = 0.001). A negative correlation between BDNF levels at admission and years of crack use was observed. We did not find significant changes in TBARS levels during inpatient treatment, although the completer group tended to decrease these levels while non-completers tend to increase it. These findings suggest an association between higher levels of BDNF and better clinical outcomes in crack- cocaine users after detoxification. We believe that the variation in BDNF and TBARS found here add evidence to literature data that propose that such biomarkers could be used to better understand the physiopathology of crack- cocaine addiction.